Planetary Quotas and the Planetary Accounting Framework Comparing Human Activity to Global Environmental Limits - Meyer, Katherine (Curtin University, 2018)
Human activity is putting us at risk of altering the planet from hospitable to hostile. The Planetary Quotas are scientific limits for human activity, based on global environmental limits. The Planetary Accounting Framework is a new way to manage the Earth System using the Quotas in a poly-scalar approach. The framework allows meaningful decisions to be made at any level, and in any sector regarding policy, planning, technology and innovation, business operations, legislation and behaviour.